A secret key establishment in frequency division duplex communication systems under active attacker. Issue 5 (26th September 2018) - Allam, Ali M.
Abstract : Most of the current research on generating a secret key from wireless fading channels relies on the channel reciprocity feature of the time division duplex link between legitimate entities so that they can acquire related information from the joint wireless connection. This paper investigates the challenge of generating a shared secret key in frequency division duplex communication systems, in which there is no reciprocity between the two nodes, in the presence of an active opponent. We suggest a key generation algorithm that depends on the product of two fading coefficients. We additionally look at the effects of an interfering adversary on the suggested key establishment scheme and solve the problem of evaluating the key rate for a scheme depending on virtual channel gain. We illustrate an adversary model using an optimal attacking strategy to minimize the rate of generating a shared secret key for our suggested algorithm. Additionally, we identify the suitable channel conditions for the non‐zero rate in the existence of an interfering adversary using simulation results.